Kampung Ramadhan Jogokariyan (KRJ): Peran Manajemen Masjid dalam Pariwisata Ramah Muslim dan Ekonomi Lokal - Wahyu Wibowo; Adi Ariga; Siti Nur Azizah; Panggabean, Nur Azizah; Nur Rahmi Irfaniah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to analyze the role of Jogokariyan Mosque management in increasing Muslim-friendly tourism and community economic growth in Jogokariyan Ramadhan Village (KRJ). The method used is quantitative descriptive, with primary data collection through questionnaires distributed to 99 respondents, using a Likert scale. Data analysis was carried out using the SMART-PLS version 4.0 program. The results of the study indicate that: (1) There is a positive and significant influence of mosque management on the development of Muslim-friendly tourism; (2) There is a positive and significant influence of mosque management on community economic growth; and, (3) Muslim-friendly tourism does not significantly affect community economic growth during the KRJ program. These findings indicate that the active role of mosque management in managing religious and social activities contributes to increasing Muslim-friendly tourism, which in turn has a positive impact on the local economy. However, other factors may mediate the relationship between Muslim-friendly tourism and community economic growth, so further research is needed to identify these variables.